A Distributionally robust game approach for integrated energy systems with prosumer interactive transactions - Dong, Lei; Li, Yang; Zhang, Tao; Wang, Zibo; Pu, Tianjiao (Applied energy, 2025)
The access of prosumers in the integrated energy system (IES) has great potential in improving system flexibility and economic operation. However, due to the complex coupling relationship and interest competition among different subjects, and the participation of renewable energy, this brings new challenges to the coordinated optimization operation of IES. To address this problem, this paper proposes a DRO-Stackelberg-Nash game model considering the uncertainty of renewable energy and the interaction of multiple stakeholders. The model takes the IES operator as the upper-level leader, considers its carbon capture system and power-to-gas device, and pursues low-carbon economic operation; the prosumers are the lower-level followers, participate in the upper-level decision-making in a cooperative manner, and realize the distribution of cooperative benefits based on asymmetric Nash bargaining theory. Secondly, the distributionally robust method is introduced to deal with the uncertainty of renewable energy, and it is nested in the above-mentioned game framework, which effectively realizes the balance of interests of different subjects under uncertainty scenarios. Finally, a step-by-step solution algorithm was developed to solve the model, which allows us to replace the lower-level prosumer model with KKT conditions in the first step, transform the two-level optimization problem into a single-level problem, and then use C&CG to obtain the optimal solution of the model; on this basis, the ADMM algorithm is used in the second step to solve the payment price between prosumers. Case studies show that the proposed method has good results in improving economic performance and reducing carbon emissions. •For prosumers with interactive transactions, a Stackelberg-Nash game method is proposed to effectively manage them.•A DRO-Stackelberg-Nash game model is used to deal with the uncertainty in the game process.•A step-by-step solution algorithm is introduced for solving the model effectively.